2019
DOI: 10.1136/bjsports-2018-100045
|View full text |Cite
|
Sign up to set email alerts
|

Including the Nordic hamstring exercise in injury prevention programmes halves the rate of hamstring injuries: a systematic review and meta-analysis of 8459 athletes

Abstract: Research questionDoes the Nordic hamstring exercise (NHE) prevent hamstring injuries when included as part of an injury prevention intervention?DesignSystematic review and meta-analysis.Eligibility criteria for selecting studiesWe considered the population to be any athletes participating in any sporting activity, the intervention to be the NHE, the comparison to be usual training or other prevention programmes, which did not include the NHE, and the outcome to be the incidence or rate of hamstring injuries.An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
162
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(177 citation statements)
references
References 40 publications
5
162
0
10
Order By: Relevance
“…One such training strategy is eccentric training, with a typical representative exercise being the Nordic hamstring exercise (NHE). 5 Indeed, programs that include the NHE induce favorable changes in established modifiable HSI risk factors (eg, eccentric knee flexor strength, BFlh fascicle length 6 ) and reduce HSIs by up to 51%. 5 However, it should be noted that the NHE is a knee-dominant movement performed with neutral hip position (0° hip flexion) and with limited knee joint range of motion due to participants' lack of eccentric knee flexor strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One such training strategy is eccentric training, with a typical representative exercise being the Nordic hamstring exercise (NHE). 5 Indeed, programs that include the NHE induce favorable changes in established modifiable HSI risk factors (eg, eccentric knee flexor strength, BFlh fascicle length 6 ) and reduce HSIs by up to 51%. 5 However, it should be noted that the NHE is a knee-dominant movement performed with neutral hip position (0° hip flexion) and with limited knee joint range of motion due to participants' lack of eccentric knee flexor strength.…”
mentioning
confidence: 99%
“…5 Indeed, programs that include the NHE induce favorable changes in established modifiable HSI risk factors (eg, eccentric knee flexor strength, BFlh fascicle length 6 ) and reduce HSIs by up to 51%. 5 However, it should be noted that the NHE is a knee-dominant movement performed with neutral hip position (0° hip flexion) and with limited knee joint range of motion due to participants' lack of eccentric knee flexor strength. As a result, NHE (a) does not enable eccentric strengthening at hamstring lengths that are similar to the lengths achieved in the late swing phase of the sprinting and (b) has limited potential in eliciting high strains and high negative work in biarticular hamstring MTUs.…”
mentioning
confidence: 99%
“…Hamstring strains frequently occur in camogie 1 and in a recent systematic review, programs that include Nordic hamstring curls have been found to half the amount of hamstring strains sustained. 26 However, four out of five elite European soccer teams did not complete the Nordic hamstring curl exercises, despite 88% of clubs being familiar with the Nordic hamstring curl exercise programme. 27 Some coaches reported that it was not easy to get players to complete the programme and that it causes muscle soreness in players.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical literature has suggested several strengthening exercises for the hamstring and gluteal muscle groups, including the hamstring curl, single-leg extension, Roman chair exercise, and Nordic exercise (McAllister et al, 2014;Park and Yoo, 2014;van Dyk et al, 2017). Recent findings have demonstrated the biomechanical effectiveness and practical benefits of the Nordic exercise (van Dyk et al, 2019;Whyte et al, 2019). This exercise (also called the "Russian hamstring exercise") can be performed with a partner without any substantial equipment (Ebben, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This exercise (also called the "Russian hamstring exercise") can be performed with a partner without any substantial equipment (Ebben, 2009). Although previous studies have noted several advantages of the Nordic exercise (Ebben, 2009;McAllister et al, 2014;van Dyk et al, 2019;Whyte et al, 2019), few reports have investigated variations of this exercise.…”
Section: Introductionmentioning
confidence: 99%